A proposal to overcome the speaking-related problems that ninth-graders in Escuela República Oriental del Uruguay in San Salvador in the academic year of 2015 - Flores Salazar, Irma Beatriz; Hernández Hernández, Liseth Abigail; Rodríguez Castillo, Josselyn Beatriz; Llanes Márquez López, Jorge Homero; Llanes Márquez López, Jorge Homero (San Salvador : Universidad de El Salvador, 2016)
The researchers consider that speaking English represents one of the most important tools to succeed in today´s society. Besides other skills and knowledge, the researchers consider that speaking is one of the most influencing factors while applying for a job or sustaining a particular work position under the condition of advancing in the language level. According to the last statistics from the employment ministry of El Salvador, there were more job opportunities for people who speak English during the year 2014 than in the past years. Indeed, nowadays knowing and managing a foreign language is a necessity for Salvadoran people. The main reason for working on this research project development is to find the most troublesome speaking-related problems and to consult experts, resources, and bibliographical pieces of information that help the researchers not only to deal with the problem under study, but also to suggest solutions to improve the speaking–related situations. Undoubtedly, speaking English plays a crucial role at the present time in El Salvador. Therefore, in this research project the researchers concentrate on speaking–related problems and on the communicative activities which might be helpful for English teachers to enhance their students´ communicative skills.
Tesis (Licenciatura en Idioma Inglés Opción Enseñanza) -- Universidad de El Salvador, San Salvador, 202016
Keywords: Enseñanza del idioma inglés